Does Religion Hinder Creativity? A National Level Study on the Roles of Religiosity and Different Denominations - Liu, Zhen; Guo, Qingke; Sun, Peng; Wang, Zhao; Wu, Rui (Frontiers in Psychology, 2018)
Creativity plays an irreplaceable role in economic and technological development. It seems that religion has a negative association with creativity. If it is true, how can we interpret the rapid development of human society with religious believers comprising 81% of global population? Based on the datasets of the World Values Survey and the Global Creativity Index, this study examined the effects of different religions/denominations on national creativity, and the moderation effect of gross domestic product per capita (GDPpc) in 87 countries. The results showed that: (1) religiosity was negatively associated with creativity at national level; (2) Proportions of Protestant and Catholic adherents in a country were both positively associated with national creativity, while proportion of Islam adherents was negatively associated with national creativity; (3) GDPpc moderated the relationships of creativity with overall religiosity, proportion of Protestant adherents, and proportion of Catholic adherents. In countries with high GDPpc, national religiosity and proportion of Islam could negatively predict national creativity, and proportion of Protestants could positively predict national creativity; in countries with low GDPpc, these relationships became insignificant. These findings suggest that national religiosity hinders creativity to a certain extent. However, some denominations (i.e., Protestant and Catholic) may exert positive influences on creativity due to their religious traditions and values. The religion-creativity relationship at national level only emerges in affluent countries.